2017
DOI: 10.1039/c7ra04044j
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid organic–inorganic three-dimensional cathode interfacial material for organic solar cells

Abstract: An alcohol soluble hybrid organic–inorganic three-dimensional material POSS-FN has been synthesized and assessed as a cathode interlayer within organic solar cells consisting of a PBDT-BT:PC61BM bulk heterojunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Similar phenomena were observed before, and it was ascribed to the dipole formation only. 29,51 As intermolecular n-doping process was found between CIMs and the acceptor, both n-doping process and dipole formation may be responsible for the WF changes. Anyway, PSM has no n-doping effect and the reduction of WF should come from dipole formation only, so its WF reduction is the smallest, while the other two polymers of PSN and PSO display larger reduction of the WF due to their n-doping process and the dipole formation.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar phenomena were observed before, and it was ascribed to the dipole formation only. 29,51 As intermolecular n-doping process was found between CIMs and the acceptor, both n-doping process and dipole formation may be responsible for the WF changes. Anyway, PSM has no n-doping effect and the reduction of WF should come from dipole formation only, so its WF reduction is the smallest, while the other two polymers of PSN and PSO display larger reduction of the WF due to their n-doping process and the dipole formation.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
“…Later, they found that the n-doping effect of the conjugated CIM is very weak or even negligible on the non-fullerene acceptor interface. , To explore the relationship of the CIMs structure with the n-doping process and device performances, we choose nonconjugated polymers with various pendant polar groups to explore how the pendant groups interact with the acceptor through an intermolecular n-doping process. Previously we reported that a nonconjugated polymer with amine moiety work similarly to that of the typical conjugated polymer interfacial material poly­[(9,9-bis­(3′-( N , N -dimethylamino)­propyl)-2,7-fluorene)- alt -2,7-(9,9-dioctyl)­fluorene] (PFN), and thus it has potential similar to those of other cathode interfacial materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, while there is no challenge in processing ETLs on ITO, as done in inverted OSCs, using a conventional device layer stack requires the ETL to be processed on top of the photoactive layer without extreme thermal annealing steps. [ 13 ] When it comes to inorganic–organic materials, it typically plays the purpose of optimizing the surface morphology and regulating the energy level, which is beneficial for boosting device efficiency. However, in order to reduce the production cost, the preparation process of the interface layer is also particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…A polar moiety such as phosphine oxide would be expected to reduce the work function of a metal electrode by inducing an interface dipole and a vacuum level shift. 24,42,43 To investigate these effects of the BIPO and TIPO, the work functions of cathodes with and without interfacial layers were estimated with the aid of ultraviolet photoelectron spectroscopy (UPS). The secondary cut-off spectra in the low-kinetic energy region (as obtained by UPS) are shown in Figure 3a.…”
Section: ■ Introductionmentioning
confidence: 99%